# 【数学】三次根式问题

$\Huge\textsf{三次根式问题}$



### 前置知识！

$1.\sqrt[n]{ab}=\sqrt[n]{a}*\sqrt[n]{b}$

$2.a^3+b^3 = (a+b)(a^2-ab+b^3),$

$\;\;\;a^3-b^3=(a-b)(a^2+ab+b^2)$

$3.(a+b)^3 = a^3+3a^2b+3ab^2+b^3,$

$\;\;\;(a-b)^3 = a^3-3a^2b+3ab^2-b^3$



### 方法：设三次根号的部分为未知数，然后列方程。

$\texttt{例<1>}$



$\begin{cases}a-b=1(1)\\a^3-b^3=61(2)\end{cases}$

$(2)$$(a-b)(a^2+ab+b^2)=61$,

$(a-b)^2+3ab=61,$

$(1)$联立解得$a_1=5,a_2=-4,$

$\therefore x_1=80,x_2=-109.$



$\texttt{例<2>}$



$\begin{cases}a^3+b^3=4(1),\\ab=-1(2)\end{cases}$

$(1)$$(a+b)(a^2-ab+b^2)=4,$

$(a+b)[(a+b)^2-2ab+1]=4,$

$k[k^2+3]=4,$

$k^3+3k-4=0,$

$(k-1)(k^2+k+4)$

$k^2+k+4$无实数根，所以$k=1,$$a+b=1.$

$\therefore \begin{cases}ab=-1,\\a+b=1,\end{cases}$

$\therefore \sqrt[3]{2-\sqrt{5}} = \dfrac{1-\sqrt{5}}{2}.$



$\texttt{例<3>}$



$(x+7)\sqrt[3]{x+7} = 16x\sqrt[3]{x}$

$\sqrt[3]{x+7} = a,\sqrt[3]{x} = b,$

$a^3\cdot a = 16b^3\cdot b,$

$a^4 =16b^4,a=\pm2b,$

$\therefore \sqrt[3]{x+7} = 2\sqrt[3]{x},$

$x+7 = 8x,$

$x=1.$



$\texttt{例<4>}$



$\sqrt[3]{1-x + x^2} =a,$

$\dfrac{x^4}{a}-a^3=0,$

$x^4-a^4=0,$

$x=\pm a.$

$\because x>0 ,\therefore x=a.$

$\therefore \sqrt[3]{1-x + x^2}= x,$ 易得$x=1.$



$\texttt{例<5>}$



$\begin{cases} a=\sqrt{3+b}\;\Rightarrow a^2 = b+3,\;\qquad\quad \;\;(1)\\b^2 - a^3 = 9\;\Rightarrow a^3 =(b+3)(b-3)\;\;(2) \end{cases}$

$(1)$代入$(2)$得，

$a^3 =a^2(b-3),a=b-3\qquad\qquad\qquad\;\;(3)$

$(1)-(3)$得，

$a^2 -a -6 =0,a_1 = -2,a_2 = 3.$

$\because a = \sqrt{3+\sqrt{9+x}} \geq 0,\;\therefore a=3,x=27.$



$\texttt{例<6>}$

$a=\sqrt[3]{4}+\sqrt[3]{2}+1,$$\dfrac{3}{a}+\dfrac{3}{a^2}+\dfrac{1}{a^3}.$



$=(\sqrt[3]{2})^2+\sqrt[3]{2}+1,$

$\therefore (\sqrt[3]{2}-1)a=(\sqrt[3]{2}-1)[(\sqrt[3]{2})^2+\sqrt[3]{2}+1]$

$=2+(\sqrt[3]{2})^2+\sqrt[3]{2}-(\sqrt[3]{2})^2-\sqrt[3]{2}-1$

$=2-1=1.$

$\scriptsize\sout\textsf{这谁tm能想得到啊}$

$\therefore (\sqrt[3]{2}-1)a =1,\dfrac{1}{a} =\sqrt[3]{2}-1.$

$\therefore \dfrac{3}{a}+\dfrac{3}{a^2}+\dfrac{1}{a^3}$

$=3*(\sqrt[3]{2}-1)+3*(\sqrt[3]{2}-1)^2+(\sqrt[3]{2}-1)^3$



$\texttt{例<7>}$



$a^3-b^3=1,$

$(a-b)(a^2+ab+b^2)=1.$

$=\dfrac{1}{a^2+ab+b^2}$

$=\dfrac{a^3-b^3}{a^2+ab+b^2}$

$=a-b=\sqrt[3]{3}-\sqrt[3]{2}.$



$\texttt{例<8>}$



$\sqrt[3]{5+2\sqrt{13}}+\sqrt[3]{5-2\sqrt{13}}=x,$

$x^3=(\sqrt[3]{5+2\sqrt{13}}+\sqrt[3]{5-2\sqrt{13}})^3$

$=(\sqrt[3]{5+2\sqrt{13}})^3+3\sqrt[3]{5+2\sqrt{13}}*(\sqrt[3]{5-2\sqrt{13}})^2+3(\sqrt[3]{5+2\sqrt{13}})^2*\sqrt[3]{5-2\sqrt{13}}+(\sqrt[3]{5-2\sqrt{13}})^3$

$=5+2\sqrt{13}+3\sqrt[3]{5+2\sqrt{13}}\cdot\sqrt[3]{5-2\sqrt{13}}(\sqrt[3]{5+2\sqrt{13}}+\sqrt[3]{5-2\sqrt{13}})+5-2\sqrt{13}$

$=10+3\sqrt[3]{-27}(\sqrt[3]{5+2\sqrt{13}}+\sqrt[3]{5-2\sqrt{13}})$

$=10-9x.$

$\therefore x^3=10-9x,$

$x^3+9x-10=0,$

$(x-1)(x^2+x+10)=0.$

$(x^2+x+10)$无实数根，$\therefore x=1.$

$\scriptsize\sout\textsf{虽然也挺麻烦的}$

### 柿柿看！

$1.$解方程：$\sqrt[3]{5+x}-\sqrt[3]{4-x}=3.$

$2.$化简：$\sqrt[3]{10+6\sqrt{3}}.$

$3.$计算：$\sqrt[3]{20+14\sqrt{2}}+\sqrt[3]{20-14\sqrt{2}}.$

$4.$计算：$\sqrt[3]{-1+\sqrt{\dfrac{-98}{27} }}+\dfrac{5}{\sqrt[3]{-1+\sqrt{\dfrac{-98}{27} }}}.\scriptsize\sout\textsf{(大 毒 瘤}$

©️2019 CSDN 皮肤主题: 深蓝海洋 设计师: CSDN官方博客